Membuka Ruang Publik: Gerakan Demokratisasi Lokal Melalui Forum Warga dan Peran Strategis Perempuan - Juni Thamrin (Antropologi Indonesia, 2010)
This paper argues that in the era of decentralization of developmental democratization at the local level through forums involving citizens have not yet formally involved strategic roles of women. The author reviews on how women’s strategic role on the local level has not been entirely met by mechanisms of formal channels at the village level. Taking a case study in Indramayu, the author outlines issues of democratization through various citizen forums that show problems of political participation that turn out to limit the role of women. The transformation of the public decision making structure on the local level should collaboratively involve aspirations of women who are still engaged in informal political context.